Pakistan in regional and global politics - Jetly, Rajshree (New Delhi : Routledge, Taylor & Francis Group, 2009)
Contributed articles presented at a conference
Includes bibliographical references (p. [333]-349) and index
Keywords: Economic development -- Pakistan -- Congresses; Security, International -- Pakistan -- Congresses; National Security -- Pakistan -- Congresses; Pakistan -- Relations -- Congresses; Pakistan -- Politics and government -- 1988- -- Congresses